The United States leper segregation policy in the Philippines 1906-1935 - Galang, Antonio G. Jr
The existing studies on leprosy in the Philippines chiefly deal with the medical view of the disease. There is a dearth of literature on the holistic study of leprosy segregation covering the period before American colonization of the Philippines, during its implementation from 1906, until the end of the American's direct control in 1935. This is the gap that this particular study tries to fill. Aside from examining the policy of leper segregation imposed by the United States ion the Philippines, this work determines the impact of the policy on the patients, their families and the Philippine society. It, likewise, looks into the motives behind the policy. Using both primary and secondary sources, this work reveals that leprosy segregation alone was not sufficient to control leprosy contamination; that the establishment of the Culion Leper Colony as a shelter to the victims of leprosy to prevent the public from contamination proved to be an inadequate solution for the problem, especially in the early stages of policy implementation. Although there was an effort addressing the problem of leprosy, it appeared the segregation was imposed only to remove the filthy in the midst of society and not to provide the patients with the treatment and care, they so badly needed; the initial purpose was not to exterminate the dreadful disease. Apart from lack of concrete plans, when the isolation was started, those who took care of the lepers were likewise, insufficient in medical knowledge, experience, and number. The study concludes that leprosy segregation alone was inadequate to control significantly the leprosy contamination and proliferation in the Philippines. It had to be combined with an effective method of treatment and efficient management. It was during Governor-General Wood that significant advancement in leprosy treatment in the Philippines occured. With the development of an effective treatment in 1928, lepers finally no longer had to suffer from permanent isolation in Culion. Rather, they enjoyed the company of their loved ones while undergoing treatment. In general, the 29 years of leper segregation and its accompanying measures under the American regime brought about enormous changes in the life of the lepers, their families and the Philippine society in general. This change includes the acculturation of the patients to the American concept of health and hygiene, the intensification of leprosy stigma and the eradication of leprosy in the Philippines. Certainly, the Americans had their own share of invaluable learning and realization too, such as being proactive rather than reactive in implementing a policy.